An evaluation of portable high-efficiency particulate air filtration for expedient patient isolation in epidemic and emergency response - Mead, Kenneth (Ann Emerg Med, 2004)
Extraordinary incidents resulting in airborne infectious disease outbreaks could produce patient isolation requirements that exceed most hospitals' capacity. This article investigates expedient methods to establish airborne infection isolation areas using a commercially available portable filtration unit and common hardware supplies. The study was conducted within a conventional, nonisolation hospital room, and researchers evaluated several airborne isolation configurations that did not require building ventilation or structural modifications. A portable high-efficiency particulate air filtration unit and full-length plastic curtains established a “zone-within-zone” protective environment using local capture and directional airflows. The cost of constructing the expedient configurations was less than US$2,300 and required fewer than 3 person-hours to construct. A medical nebulizer aerosolized polystyrene latex microspheres to generate respirable condensation nuclei. Aerosol spectrometers sized and counted respirable particles at the source patient and health care worker positions and in areas outside the inner zone. The best-performing designs showed no measurable source migration out of the inner isolation zone and mean respirable particle counts up to 87% lower at the health care worker position(s) than those observed directly near the source patient location. Investigators conclude that with careful implementation under emergency circumstances in which engineered isolation rooms are unavailable, expedient methods can provide affordable and effective patient isolation while reducing exposure risks and potential disease transmission to health care workers, other patients, and visitors.